Strategi Pengembangan Model Pembiayaan Pendidikan Inklusi : Solusi Dukungan Finansial Berkelanjutan - Nafarin, Wahyudi; Eljohn, Grace; Sari, Yunita; Haryaka, Usfandi; Mulawarmana, Widyatmike Gede (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Inclusive education is increasingly recognized as a fundamental aspect of equitable and quality education for all. However, its implementation often faces financial challenges, particularly in ensuring sufficient resources to accommodate learners with diverse needs, including those with disabilities. The urgency of this research lies in the growing demand for inclusive educational practices and the lack of sustainable financial models to support them effectively. This study aims to develop a sustainable funding model strategy for inclusive education by exploring innovative financial solutions such as public-private partnerships, community fundraising initiatives, and more efficient budget allocation mechanisms. Utilizing qualitative methods including case studies, policy analysis, and in-depth interviews with policymakers, educators, and financial experts this research reveals that inclusive education funding can be significantly improved through collaborative and diversified funding sources. The findings show that successful implementation often involves multi-stakeholder engagement, transparency in fund management, and adaptive financial planning. The implications of this research are far-reaching. It provides practical and scalable recommendations for policymakers, educational institutions, and non-governmental organizations to design and implement funding strategies that are both sustainable and equitable. These strategies not only improve access to inclusive education but also strengthen the overall quality and resilience of education systems, particularly in under-resourced regions.